KARAKTERISTIK FISIS DAN MEKANIS GLULAM JATI, MANGIUM DAN TREMBESI - Nurwati Hadjib; Abdurachman; Efrida Basri (BRIN Publishing, 2015)
This paper studies the physical and mechanical characteristics of the glued-laminated (glulam) beams made from small diameter of three fast growing species i.e. teak (Tectona grandis L.f), mangium (Acacia mangium Willd.) and trembesi/monkeypod (Samanea saman Merr.) using water based polymer isocyanate (WBPI) as a binder. Six plies of wood combination species were laminated into final dimension of 6 cm × 12 cm × 300 cm. Each laminate was graded using Machine Stress Grading (Pantek, plank sorter) to determine its Modulus of Elasticity (MOE). Cross-section of two type of glulam beam was 6 cm × 12 cm, arranged of various widths and based on values of laminate MOE. Results show that the average and range value of the glulam density were 0.658 g/cm³ and 0.557-0.821 g/cm³, with the moisture content of 14.6% (13-16.8%). The average of the glulam modulus of elasticity and modulus of rupture were 75.51 (37.016-120.446) kg/cm² and 494 (145-750) kg/cm² respectively. The glulam made from teak has better MOE and MOR performances compared to those of mangium and trembesi. In general, the results showed that almost all of glulam beams tested meet requirement of JAS (Japanese Agricultural Standard) 2007 for structural glulam in moisture content, MOE, MOR, and shear strength. The glulam qualities can be classified into E65-E95-F225-F270, except for several species combination beams. Based on the strength classified and the ratio of S/W, the glulam can be used as a construction material except glulam teak-trembesi (preserved or unpreserved) and the unpreserved trembesi-trembesi. The three types of glulam can be utilized for the lightweight construction.